An unusual presentation of central cervical fibroid: a case report - Samal, Sunil Kumar; Rathod, Setu; Rajsekaran, Anandraj; Rani, Reddi (International Journal of Research in Medical Sciences, 2017)
Leiomyomas are most common benign gynaecological tumour. Most of the fibroids are situated in the body of the uterus, but only in 1-2% cases, they are confined to cervix. We report a case of a 48-year old female who presented with gradual abdominal distension for one year. Abdominal examination revealed a huge mass of 28 week size pregnant uterus with well-defined margins except the lower poles which cannot be reached, restricted mobility from above downwards but can be moved from side to side, non-tender and solid in inconsistency. Ultrasound revealed a large abdominopelvic mass with solid and cystic component. On exploratory laparotomy, a huge central cervical fibroid was found and total abdominal hysterectomy with bilateral salpingoophorectomy was done after enucleation of the fibroid by Rutherford Morrison’s technique. Histopathological examination confirmed the diagnosis of cervical fibroid with hyaline and cystic degeneration. The postoperative was uneventful.